The Role of the Teacher in Implementing the Project to Strengthen the Profile of Pancasila Students - Desmarianti, Riri; Ahyani, Nur; Suherman, Suherman (Graduate Program Magister Manajemen Pendidikan, 2024)
This research aims to describe and determine the role of teachers in implementing the Project for Strengthening the Profile of Pancasila Students at SMA Negeri 1 BaNyausin III. Data collection tools use interviews, documentation, observation, and literature review methods. Data analysis uses descriptive qualitative analysis with stages of data collection, data reduction, data presentation, and conclusion drawing. The research results stated that. The teacher’s role in implementing the Pancasila Student Profile Strengthening Project at SMA Negeri 1 Banyuasin III is to be a student guide, and facilitator and design activities based on the character values of the Pancasila Student Profile. Implementation of the Project for Strengthening the Profile of Pancasila Students. The obstacles faced are limited resources, lack of support and understanding as well as lack of student participation in the Project for Strengthening the Pancasila Student Profile. The solution to several obstacles is the efficient use of resources and improving communication and understanding with all stakeholders, including teachers, students, parents, and the community.